"CHEMICAL COMPOSITION OF ESSENTIAL OIL ISOLATED FROM THE RHIZOMES OF KAEMPFERIA GALANGA L." - AJAY KUMAR, (International Journal of Pharma and Bio Sciences, 2014)
The aim of the present study was to evaluate the chemical composition of essential oil isolated from the rhizomes of Kaempferia galanga L. The essential oil was isolated from the dried rhizomes of Kaempferia galanga L. by steam distillation method and analyzed by gas chromatography-mass spectrometry (GC-MS) technique. Total fifty constituents were identified from rhizome oil constituting 97.19% of the oil. The major constituents of the oil were ethyl cinnamate (29.48%), ethyl-p-methoxycinnamate (18.42%), γ- cadinene (9.81%), 1, 8-cineole (6.54%), δ-carene (6.19%), borneol (5.21%), ethyl-m-methoxycinnamate (2.15%), camphene (1.58%), linoleoyl chloride (1.35%) and α-pinene (1.32%). The results suggest that the essential oil and its major components possess several biological activities like antibacterial, antifungal, analgesic, anti-inflammatory, antioxidant, antiviral, antihypertensive, anticarcinogenic, antinociceptive, anti-tuberculosis and larvicidal. The oil may be useful in perfumery, pharmaceuticals, and in aromatherapy as inhalants and massage to reduce anxiety, stress and depression.